2022
DOI: 10.9734/ijecc/2022/v12i1130967
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Biofertilizers and Zinc Levels on Growth and Yield of Maize (Zea mays L.)

Abstract: The study aims to highlights the effect of different biofertilizers and zinc levels on growth and yield of maize (Zea mays. L). The study was conducted during Rabi 2021 at crop Research farm, Department of Agronomy, SHUATS, Prayagraj, (U.P), India. The soil of this experimental plot was sandy loam in texture, nearly neutral in soil reaction (pH 7.1), in low organic carbon (0.36%), available N (171.48 kg/ha), available P (15.2kg/ha), available K (232.5 kg/ha). This experiment was performed in Randomised Block D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The superiority of the catalytic treatment with hydrogen peroxide in radicle length (Table 5) may explain the reason for its superiority in seedling dry weight. This result is consistent with the results obtained by [18,19] who indicated that stimulating maize seeds with hydrogen peroxide led to a significant increase in seedling dry weight. The results of Table 7 indicate that Al-Maha and Al-Nahrain cultivars gave the highest average dry weight of the seedling, which amounted to 0.194 gm for each of them respectively, compared to Baghdad and Al-Fajr, which gave the lowest average of 0.180 gm for each of them, respectively.…”
Section: Seedling Dry Weight (Gm)supporting
confidence: 93%
See 1 more Smart Citation
“…The superiority of the catalytic treatment with hydrogen peroxide in radicle length (Table 5) may explain the reason for its superiority in seedling dry weight. This result is consistent with the results obtained by [18,19] who indicated that stimulating maize seeds with hydrogen peroxide led to a significant increase in seedling dry weight. The results of Table 7 indicate that Al-Maha and Al-Nahrain cultivars gave the highest average dry weight of the seedling, which amounted to 0.194 gm for each of them respectively, compared to Baghdad and Al-Fajr, which gave the lowest average of 0.180 gm for each of them, respectively.…”
Section: Seedling Dry Weight (Gm)supporting
confidence: 93%
“…The reason for the increased radicle length of seeds stimulated by hydrogen peroxide may be due to its role in increasing cells findings and elongation and their division [18]. This result is consistent with the results obtained by [19], who indicated that stimulating maize seeds with hydrogen peroxide led to a significant increase in radicle length. Al-Maha cultivar was significantly superior with the highest radicle length of 14.42 cm compared to Fajr cultivar, which gave the lowest average radicle length of 13.26 cm, and did not differ significantly from Al-Nahrain cultivar, which gave 13.46 cm (Table 5).…”
Section: Radicle Lengthsupporting
confidence: 87%
“…Subsequently, they underwent a battery of chemical analyses following standardized procedures. Organic carbon content was assessed using the Walkey and Black rapid titration method (Walkley and Black 1934) [76] , available nitrogen via the alkaline permanganate method (Subbiah and Asija 1956) [59] , available phosphorus using the calorimetric method (Olsen et al, 1954) [38] , and available potassium through flame photometer (Hanway and Heidal 1953) [10] , soil pH through a glass electrode pH meter (Piper 1967) [48] and Electrical conductivity was measured using Solubridge method (Black 1965) [6] . The data collected from both the stover and soil analyses were meticulously compiled and interpreted to glean valuable insights into the effects of the different treatments on nutrient uptake, crop yield, and soil health.…”
Section: Methodsmentioning
confidence: 99%
“…India holds a prominent position among maize-producing countries, ranking 4 th globally in cultivated area and 7 th in production, contributing around 4% of the world's area and 2% of total maize production [48][49] . A significant portion of maize production in India, roughly 47%, is allocated for poultry feed, while 13% serves as livestock feed and for human consumption each, with additional percentages utilized for industrial purposes, starch production, processed foods, and export (Raghuwanshi et al, 2023a;Yadav et al, 2023a) [43][44][77][78][79] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that applying nitrogen fertilizer to maize greatly increases grain output (Sharma et al, 2019). Moreover, it has been discovered that zinc levels and biofertilizers work together to enhance maize production and growth (Sasank & Dawson, 2022). According to research, there are some combinations of organic manure and mineral and nano nitrogen fertilizers that can boost maize plant height, grain production, and harvest index (Khalil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%